Fefferman's Inequality in Weighted Morrey Spaces (Contemporary Mathematics, 2025)
We prove Fefferman's inequality in weighted Morrey spaces in this paper. More precisely, for the weight w belonging to booth A1 and ∆2, κ = (n−2p)/n, and f belonging to the weighted Morrey space Lp,κ(w), we prove that there exists a positive constant C such that the following inequality holdsfor every ϕ ∈ C0∞(Rn).
Keywords: Morrey spaces; weight; weighted Morrey spaces; Fefferman's inequality; maximal operator